1991
DOI: 10.1108/eb059337
|View full text |Cite
|
Sign up to set email alerts
|

Sound for Processing Food

Abstract: Ultrasound is simply a name given to sound waves whose frequency (pitch) is too high to be detected by the human ear. The use of low‐intensity ultrasonic waves in level measurement, flow detection, and medical imaging is well known. Here, a pulse of ultrasound is used to ‘probe’ the sample under investigation; comparison of the pulse shape before and after transmission, and a measurement of the transit time in the sample can provide information on many physical parameters. For these applications, the intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…via a biochemical effect (Boistier-Marquis, Lagsir-Oulahal, & Callard, 1999). A pilot study involving sirloin steak (Roberts, 1991) showed that sonicating beef muscle at 2 W·cm 2 for 2 h at 40 kHz produced damage to the perimysial connective tissue, resulting in improved eating texture.…”
Section: Meat Tenderizationmentioning
confidence: 99%
“…via a biochemical effect (Boistier-Marquis, Lagsir-Oulahal, & Callard, 1999). A pilot study involving sirloin steak (Roberts, 1991) showed that sonicating beef muscle at 2 W·cm 2 for 2 h at 40 kHz produced damage to the perimysial connective tissue, resulting in improved eating texture.…”
Section: Meat Tenderizationmentioning
confidence: 99%
“…While some authors (Jayasooriya, Bhandari, Torley, & D' Arey, 2004) assert that prolonged exposure to high-intensity ultrasonic waves causes a significant tenderising of the meat, others have failed to confirm this effect (Lyng, Allen, & McKenna, 1997;Lyng, Allen, & McKenna, 1998a;Lyng, Allen, & McKenna, 1998b). One study showed that sonication of beef muscle with an intensity of 2 Wcm -2 for 2 h at a frequency of 40 kHz damages the perimysium resulting in improved texture (Roberts, 1991). To observe changes in maturation, Pohlman, Dikeman, & Zayas (1997a) applied ultrasound (20 kHz, 22 Wcm -2 ) for 0.5 or 10 min to shear pectoral muscles that had been vacuum-packed and ripened for 1, 6 or 10 d. The sonicated muscles showed reduced hardness with no effect of sonication time or storage of packed meat on weight loss, hardness or sensory characteristics.…”
Section: Tendernessmentioning
confidence: 99%
“…Power ultrasound treatment (sonication), commonly operated at the frequency range of 20-100 kHz in the presence of a liquid medium, is a proven technology for cleaning mechanical parts or electronic circuit boards (Roberts 1991;Mason 1993;Povey and Mason 1997;Patist and Bates 2008). It has also potential application to food surface washing (e.g., decontamination of fresh produces), extraction of antioxidants from plant tissues, cell disruption, liquid degassing, and homogenization of emulsions (McClement 1995;Seymour et al 2002;Piyasena et al 2003;Albu et al 2004).…”
Section: Introductionmentioning
confidence: 99%